Prosthodontic rehabilitation of partial edentulism: Fixed-Removable approach - Zainon, Noor A.; Maniam, Haswinee; Bidin, Rosli; Ithnin, Noorhaizad (Indonesian Journal of Prosthodontic, 2025)
BACKGROUND: Effective history-taking and comprehensive clinical investigations play a vital role in systematic treatment planning process for a successful treatment outcome. OBJECTIVE: This case report highlights prosthetic rehabilitation utilizing milled featured fixed-removable prostheses taking into account patient concerns to achieve aesthetically pleasing outcome without surgical intervention. CASE REPORT: A 68-year-old Malay female was unsatisfied with her maxillary partial acrylic denture and requested for a substitute. Several treatment options were discussed to replace the multiple missing teeth on both arches. The implant-retained prosthesis was not considered as an ideal treatment option due to the patient's financial constraint and reluctance for surgical intervention. Combination of fixed-removable prostheses were planned. The maxillary removable partial cobalt-chrome denture was fabricated with milled features of anterior fixed dental prosthesis to enhance the retention, support and stability of the prosthesis. Mandibular partial cobalt-chrome denture with composite build-up on attrited anterior teeth were fabricated as a definitive treatment plan. CONCLUSION: This prosthodontic management was able to provide satisfactory aesthetic and functional outcome thus achieving a mutually protected occlusion scheme. Regular prostheses maintenance and oral hygiene instructions will enable the patient to perform adequate plaque removal. Ultimately, meticulous case selection is essential to achieve favourable longevity of the prostheses. Keywords: Dental prostheses, fixed-removable prostheses, milled features, partially edentulous, cobalt-chrome denture